Methodological Approaches to Optimizing the Debt Policy of Ukraine in the Financial Security Context - Bondaruk, T. H.; Bohrinovtseva, L. M.; Bondaruk, O. S. (Statistics of Ukraine, 2025)
The article underscores the relevance of studies devoted to problems of debt policy in Ukraine from its optimization perspective. The need to reform the domestic debt policy on the basis of advanced methodological approaches is substantiated. The current state of the public debt in Ukraine was analyzed, with outlining the main macroeconomic factors determining its growth and justifying the necessity in elaborating effective strategies for management of public borrowing. It is emphasized that keeping the financial system stable requires a rational utilization of debt resources, a decreased dependence on external financing and a higher efficiency of the internal government securities market. The study is based on system analysis and methodological approaches that cover institutional reforms, restructuring of debt and expanding of financing sources. A set of actions is proposed, aimed at diversification of debt instruments, optimization of debt burden and strengthening of the financial security of the state. In particular, a possibility for implementing international practices of debt restructuring, enhancing the transparence of financial administration and introducing an independent monitoring of debt obligations is discussed. Key improvements in the public borrowing scheme were identified, e.g., strengthening control over the efficiency of borrowed funds, implementing new approaches to regulation of debt guarantees, ensuring the stable access to international capital markets and stimulating the expansion of internal financing sources. Special emphasis is put on the influence of debt policy on the macroeconomic stability, which will be crucially important in the postwar period of economic recovery in Ukraine. It was demonstrated that an efficient debt policy had to rely on a holistic approach to public debt management, combining strategic planning, financial control and adaptability to change in the global economy. The importance of coordinating budgetary and monetary policies, to avoid a debt crisis and enhance the investment attractiveness of Ukraine, is highlighted. The implementation of crisiscombat measures aimed to prevent an excessive debt burden will help minimize risks and threats to the financial security of the state and stabilize the economic development. Implemented international practices and transparent financial administration schemes, along with the expanded internal government securities market, will lay the grounds for strengthening the financial security of the state and stabilizing the economic system in medium and longterm perspective.